The Discourse Of Integrated Quality Management System Of Education In Industrial Revolution 4.0 Era - Herman, Herman (CV. Inara, 2021)
This article aims to describe the discourse of integrated quality management system of education in the industrial revolution 4.0 era. The advancement of information, communication and technology is an opportunity and hope to implement qualified and competitive educational programs by utilizing automation technology and cyber technology. This study used a qualitative method with a descriptive approach through library research. The writing technique was carried out through several stages starting from data collection to data processing and analysis stage that were considered relevant and had relationship with the problem. The results of this study indicate that the integrated quality management system of education in the industrial revolution 4.0 era can realized through: 1) the planning of qualified educational program, 2) organizing integrated human resource, 3) flexible and transparent communication, 4) harmonious and comfortable coordination, and 5) tight and accountable supervision.